2010
DOI: 10.1016/j.oraloncology.2010.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of oral cavity squamous cell carcinoma in pediatric patients

Abstract: Background-Oral cavity squamous cell carcinoma (OCSCC) is uncommon in young patients and rare in the pediatric population. OCSCC is believed to behave aggressively in this age group, but the existing literature is limited to case reports. The objective of this study was to compare survival outcomes in pediatric and adult patients with oral cavity squamous cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 32 publications
1
18
0
2
Order By: Relevance
“…Among the 16 studies that associated SCC to the oral cavity, seven used only lesions in the tongue (3,6,8,12,13,15,20) as inclusion criteria; nine included other locations, of which six identified the tongue as the site of highest incidence (7, 9-11, 14, 16) , and just two observed predominance on the floor of mouth (18,21) . Concerning the relationship with harmful habits, nine investigations demonstrated association between tobacco and/or alcohol use and OSCC, of which six presented positive association (7,10,11,16,18,19) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the 16 studies that associated SCC to the oral cavity, seven used only lesions in the tongue (3,6,8,12,13,15,20) as inclusion criteria; nine included other locations, of which six identified the tongue as the site of highest incidence (7, 9-11, 14, 16) , and just two observed predominance on the floor of mouth (18,21) . Concerning the relationship with harmful habits, nine investigations demonstrated association between tobacco and/or alcohol use and OSCC, of which six presented positive association (7,10,11,16,18,19) .…”
Section: Resultsmentioning
confidence: 99%
“…Five of the 10 papers about the tumor-node-metastasis (TNM) Staging System indicated that a large amount of patients were diagnosed as T1 and/or T2 (8,(13)(14)(15)20) , being stages T3 and T4 (extensive tumors) predominant in other works (7,(10)(11)(12)18) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, only patients with localized, completely resectable tumors have been successfully treated: 1/9 SCC of oral cavity. However, in previous studies, survival rates of oral cavity SCC were higher: 70% 5y-OS in the Memorial SloanKettering Cancer Centre series (10 tongues SCC, 3/10 with lymph node involvement) [22] and 75.3% 5y-OS in the SEER series (54 oral cavities SCC, 40% with lymph node spread) [23]. Lower OS may be explained in our series by more frequent lymph node involvement at diagnosis and the absence of radical surgery in most patients.…”
Section: Discussionmentioning
confidence: 83%
“…Only 2/7 patients with FL-HCC and 1/5 HCC were alive with a follow-up of 47, 77 and 74 months but after multiple recurrences treated with various combined therapies (multiple surgeries, chemotherapy, hyperthermic intraperitoneal chemotherapy, inhibitor tyrosine kinase, radiofrequency). The median survival of patients was 26 months (12-78) for FL-HCC and 16.5 months (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) for HCC.…”
Section: Liver Carcinomamentioning
confidence: 99%